Mobile Service Delivery: a systematic literature review of m-Government in South Africa - Maseloanyane, Theo (Department of Political Studies, 2024)
The proliferation of Information and Communication Technologies (ICTs) has transformed how governments deliver public services to citizens. However, research has highlighted the inadequacy of electronic government (e-government) to improve public service delivery, particularly in the developing world. The ubiquitous nature of mobile phones presents the potential to bridge the digital divide and make public services more accessible to everybody through m-government. Against this backdrop, the South African government has prioritised the implementation of m-government to improve public service delivery and achieve its universal access mandate. However, the potential for South Africa's m-government programs to bring about greater digital inclusion remains largely unexplored. Accordingly, the objective of this paper is to examine whether South Africa's m-government programs have indeed made public services more accessible to everybody, and to highlight any access barriers. A systematic literature review was conducted to search, analyse and synthesise twenty studies on this topic. The research found that South Africa's m-government programs have been successful in creating access points for service delivery, and implementors have taken an active role in curbing digital exclusion by embedding skills training into their programs. Nevertheless, there are challenges that prevent South Africa's m-government programs from achieving the universal access objective. There remains a lack of affordability, sustainability, scalability and an overall m-government policy, which have contributed to the haphazard implementation of m-government programs in the country. This paper recommends that the government should have a more integrated approach in the coordination and implementation of m-government if it is to realise universal digital inclusion.